2017
DOI: 10.1080/09540121.2017.1417537
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to HIV care and its determinants in the late HAART era: a systematic review and meta-analysis

Abstract: Poor engagement into HIV care limits the effectiveness of highly active antiretroviral therapies (HAART) to improve survival and reduce transmission. The design of effective interventions to enhance linkage to care is dependent on evidence about rates of entry into HIV care. This is a systematic review and meta-analysis on linkage measurement and its determinants in the late era of HAART (post-2003), in high-income countries. We searched the PubMed and Web of Science databases, restricting our sample to the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…If sufficient scale can be reached, partner services, in particular, might be effective. 27,28 Other interventions with a more limited evidence base include testing in non-health-care settings, 29 particularly self-testing; 30,31 PrEP for people who inject drugs 32 and heterosexuals at high risk of infection; 33 testing in correctional settings 34 and transitional care support, 35 linkage to care programmes, 36 and low-barrier care delivery; 37 and e-health solutions to improve ART persistence. 38,39 Furthermore, we focused on evidencebased interventions, while remaining agnostic about the capacity or specific circumstances of public health departments.…”
Section: Figure 2: Projected Reductions In Hiv Incidencementioning
confidence: 99%
“…If sufficient scale can be reached, partner services, in particular, might be effective. 27,28 Other interventions with a more limited evidence base include testing in non-health-care settings, 29 particularly self-testing; 30,31 PrEP for people who inject drugs 32 and heterosexuals at high risk of infection; 33 testing in correctional settings 34 and transitional care support, 35 linkage to care programmes, 36 and low-barrier care delivery; 37 and e-health solutions to improve ART persistence. 38,39 Furthermore, we focused on evidencebased interventions, while remaining agnostic about the capacity or specific circumstances of public health departments.…”
Section: Figure 2: Projected Reductions In Hiv Incidencementioning
confidence: 99%
“…Almost half (21/43) of the included studies included data on PWID. 17 Injecting drug use (IDU) was significantly associated with delayed linkage, with a risk of up to two times greater compared to non-PWID. Furthermore, mental illness and having hepatitis B or C were also associated with delayed entry into HIV care.…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, we used the same software to subject the remaining 4999 articles to screening based on the aforementioned criteria. As part of our review process, we identified 19 articles that were systematic reviews of the literature about HIV and substance use and therefore relevant to the topic of this review (Abebe Moges, Olubukola, Micheal, & Berhane, 2020; Ahmed et al, 2018; Arrivillaga, Martucci, Hoyos, & Arango, 2013; Bazzi et al, 2019; Casale, Carlqvist, & Cluver, 2019; Feelemyer, Des Jarlais, Arasteh, & Uusküla, 2015; Glick et al, 2020; Govindasamy, Ford, & Kranzer, 2012; Hudelson & Cluver, 2015; Larney et al, 2017; Locher, Messerli, Gaab, & Gerger, 2019; Low et al, 2016; Mistler, Copenhaver, & Shrestha, 2021; Nachega et al, 2012; Nguemo Djiometio et al, 2020; Paquette & Pollini, 2018; Perelman, Rosado, Ferro, & Aguiar, 2018; Uthman, Oladimeji, & Nduka, 2017; Velloza et al, 2020). We examined these articles and their reference lists and found no additional studies in the reference lists that met our inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%